Synthesis of New Heterocyclic compounds derived from Pyrazoline-5-one compound - Rafah F. Al-Smaisim; Redha E. Al-Bayati; Abdul Hussain K. Sharba (College of Pharmacy / Mustansiriyah University, 2011)
In this work new heterocyclic pyrazolin derivatives have been synthesized from diazonium chloride salt of 4-aminobenzoic acid: firstly, Azo compounds were prepared from the reaction of an ethanolic solution of sodium acetate and calculated amount of active methylene compound namely, (ethyl acetoacetate) obtain the corresponding hydrazono derivative (1). Secondly, Cyclocondensation reaction of compound (1) with hydrazine hydrate (2) in boiling ethanol affording the corresponding pyrazoline-5-one. Then compound (2) reacted with thionyl chloride to give the corresponding acid chloride derivative(3), followed by conversion into the corresponding carboxylic acid thiosemicarbazide (4), esters (7-9), thioesters (10), (11), and amides (12-14), when treated hydrazine hydrate, thiosemicarbazide, alcohols, alkylthiol and secondary amines in dry refluxing benzene; respectively. Furthermore, 1,2,4- triazole heterocyclic ring, which might result in biologically active agents, have been prepared by refluxing thiosemicarbazide derivative (4) with sodium hydroxide solution (4%) followed acidification of the result using (10%)HCl solution. Moreover, 1, 3, 4, - thiadiazole heterocyclic ring (6) has been prepared by treatment of thiosemicarbazide derivative with concentrated sulfuric acid as cyclization agent. Finally, derivative (15) has prepared by reflux (1) with phydroxybenzaldehyde then the product reflux with 5-amino-1, 3, 4-thiadiazol-2- thiol to product (16) derivative. All structures of newly synthesized compounds have been characterized and identified via of their physical properties and spectral data analysis (IR, UV.)